2015
DOI: 10.12659/aot.892707
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation among Malaysian Muslims: The Role of Mosques

Abstract: Data collected from a survey on 653 Malaysian Muslims reveals that the main factors that hamper organ donation-related activities at the mosques in Malaysia are the lack of experts and financial resources. The level of autonomy of the mosque is also another main issue. The respondents believe that talks and dialogues are the best methods for organ donation campaigns at the mosques. Conclusions We argue that if the mosques are to play a role in imparting knowledge on organ donation, there should be ample opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tumin and colleagues ( 2015b ) surveyed 653 Malaysian Muslims from 82 mosques in Kuala Lumpur regarding their knowledge of and access to information about organ donation. They reported that 54–64 % of respondents did not have access to information at either religious sermons or lectures at mosques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumin and colleagues ( 2015b ) surveyed 653 Malaysian Muslims from 82 mosques in Kuala Lumpur regarding their knowledge of and access to information about organ donation. They reported that 54–64 % of respondents did not have access to information at either religious sermons or lectures at mosques.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that 54–64 % of respondents did not have access to information at either religious sermons or lectures at mosques. In an effort to correct this circumstance, Tumin et al ( 2015b ) have recommended that governmental funding be made available, and that faith leaders be encouraged to participate in campaigns aimed at increasing “organ donation activities at mosques” and “providing accurate information to the Malaysian Muslim community.” However, “accurate information” about living and end-of-life organ donation is then limited to include only the information that encourages donor registration among citizens (Tumin et al 2015a ). Within such a context, the recommendation of recruiting faith leaders and promoting organ donation at mosques as a public policy buttresses the problem of trustworthiness of information.…”
Section: Introductionmentioning
confidence: 99%